Hubungan Usia, Pengambilan Keputusan KB dan Sumber Informasi KB dengan Penggunaan Metode Kontasepsi Jangka Panjang Pada Wanita Usia Subur Pascasalin Di Indonesia (Analisis Data SDKI 2017) - Nenda Wulandari; Evi Martha; Jusuf Kristianto (Syntax Corporation Indonesia, 2022)
The low use of long-term contraceptive methods, especially in postpartum mothers, is caused by various factors. Postpartum family planning is a family planning service that is given after giving birth for up to 6 weeks, carried out in health care facilities carried out by professional health workers, namely specialist doctors, general practitioners and midwives. Efforts to improve family planning services, especially postpartum, are considered the right strategy because the coverage of ANC services and delivery coverage by health workers is quite high. Policies regarding family planning lead to the use of long-term contraceptive methods. This study discusses the relationship between age, family planning decision making and family planning information with the use of long-term contraceptive methods in postpartum women in Indonesia by analyzing secondary data from the 2017 IDHS. This study is a quantitative study. Cross sectional research design, with univariate and bivariate analysis. The sample in this study were women of childbearing age postpartum in Indonesia. The results of the study were that most of the respondents used the Non long-term contraceptive methods method, namely 80.2%. Most of the respondents are 15-34 years old; most of the respondents make decisions on the use of shared family planning and most of the respondents get family planning information from non-health workers. There is a relationship between age, family planning decision makers and sources of family planning information and the use of long-term contraceptive methods in postpartum mothers in Indonesia. The need for postpartum family planning counseling that involves the husband using easy-to-understand media. Increased knowledge about family planning in postpartum mothers through IEC is expected to be better so that it will affect the increase in the number of postpartum long-term contraceptive methods use